GAMBARAN KEKERASAN PADA ANAK YANG Â MEMINTA-MINTA (PENGEMIS) DI KELURAHAN PULOREJO KECAMATAN PRAJURIT KULON KOTA MOJOKERTO - Triwibowo, Heri; Frilasari, Heni (JURNAL KEPERAWATAN SEHAT, 2016)
A child doesn’t have sins, really irritable to the environment and still depend on another. Children need happy life in safe and comfort condition in order to be able play and learn to adult optimally. But most of parents force their children to work to raise family income, everytime children can disturb their growth and development. This research is aimed to know description of orphan children abuse in Pulorejo Downtown Prajuritkulon Mojokerto. This research uses descriptive method. The population of this research is all of orphan children in Pulorejo Downtown Prajuritkulon Mojokerto as many as 23 childrens, Sampling technique used is total sampling technique. The result of this research shows that orphan children abuse in Pulorejo Downtown Prajuritkulon Mojokerto is all of respondent (100%) due to emotional abuse, neglected andcommercialization, 73.9% due to physical abuse, and 26.1% due to sexual abuse.Analysis of data used univariate analyze that result frequencies distribution and percentage. Abuse to the children is really hurt physically or emotionally, sexual abuse, neglected, commercial exploitation and anothe exploitation, that cause injury and real disadvantage or potential tothe children’s health, children life, dan children’s growth and development. This abuse need better and more serious handle from associated side not only government but also society.Key words:children, abuse, orphan